2017
DOI: 10.15171/ijb.1356
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Perspectives on the Prediction of the PLP’s Epitopes involved in Multiple Sclerosis

Abstract: Background Multiple sclerosis (MS) is the most common autoimmune disease of the central nervous system (CNS). The main cause of the MS is yet to be revealed, but the most probable theory is based on the molecular mimicry that concludes some infections in the activation of T cells against brain auto-antigens that initiate the disease cascade. Objectives The Purpose of this research is the prediction of the auto-antigen potency of the myelin proteolipid protein (PLP) in multiple sclerosis. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“… 31 A recent study involving PLP's Epitopes involved in MS, found CSAVPV (in PLP 161-177 residues) among the most immunogenic regions of PLP. 32 In addition, the crystal structure of the NS5 ZikV protein reveals a conserved domain conformation of Flaviviruses, a genus that includes a variety of human pathogens such as dengue virus, yellow fever virus, WNV, Spondweni virus, and the Japanese encephalitis virus. 33 So, the presence of high identity between NS5 ZikV and PLP, an autoantigen widely implicated in the pathogenesis of MS, 34 leads us to postulate that molecular mimicry may have a role in the development of inflammatory demyelinating damage, a hallmark of the IDD produced by this genus of virus.…”
Section: Discussionmentioning
confidence: 99%
“… 31 A recent study involving PLP's Epitopes involved in MS, found CSAVPV (in PLP 161-177 residues) among the most immunogenic regions of PLP. 32 In addition, the crystal structure of the NS5 ZikV protein reveals a conserved domain conformation of Flaviviruses, a genus that includes a variety of human pathogens such as dengue virus, yellow fever virus, WNV, Spondweni virus, and the Japanese encephalitis virus. 33 So, the presence of high identity between NS5 ZikV and PLP, an autoantigen widely implicated in the pathogenesis of MS, 34 leads us to postulate that molecular mimicry may have a role in the development of inflammatory demyelinating damage, a hallmark of the IDD produced by this genus of virus.…”
Section: Discussionmentioning
confidence: 99%
“…Autoreactivity to PLP in patients with MS has been investigated in human and animal model by various groups worldwide (30). A recent study involving PLP's Epitopes involved in MS, found CSAVPV (in PLP 161-177 residues) among the most immunogenic regions of PLP (31). In addition, the crystal structure of the NS5 ZikV protein reveals a conserved domain conformation of Flaviviruses, a genus that includes a variety of human pathogens such as dengue virus, yellow fever virus, West Nile virus, Spondweni virus and the Japanese encephalitis virus (32).…”
Section: Discussionmentioning
confidence: 99%